2022-LBA-1618-ESGO A pilot study of interval cytoreductive surgery and HIPEC for advanced epithelial ovarian cancer in the UK. (27th October 2022) - Sap, Katelijn; Decruze, Bridget; O'Dwyer, Sarah; Hasan, Jurjees; Aziz, Omer; Winter-Roach, Brett
Abstract : Introduction: The Christie is one of the first UK cancer centres to offer hyperthermic intraperitoneal chemotherapy(HIPEC) to patients with advanced epithelial ovarian cancer(AEOC). Though the OVHIPEC1-trial has demonstrated longer recurrence free and overall survival for patients undergoing interval cytoreductive surgery(CRS) with the addition of cisplatin based HIPEC compared to CRS alone, this treatment is not yet offered as NHS-funded treatment. We report early follow up data on safety and feasibility of CRS+HIPEC in ovarian cancer patients at the Christie, with an analysis of comparative perioperative costs. Methods: Patients with high grade AEOC who achieved partial response to 3 or 4 cycles of neoadjuvant carboplatin-paclitaxel chemotherapy were selected for interval CRS+HIPEC. The procedure was performed by Gynaecological Surgical Oncologists in collaboration with Peritoneal Surgeons with extensive experience of CRS+HIPEC in colorectal and appendiceal malignancies. Closed HIPEC delivery technique was used. Cisplatin was perfused at 42°C for 90 minutes at 100 mg/m 2 . Results: 9 patients have undergone CRS+HIPEC for AEOC at The Christie since October 2021. By the LBA submission deadline, this will be 10. We will report on median time to surgery from chemotherapy, pre- and postsurgical PCI score, mean length of stay and CCU stay, intra- and postoperative complications and 30 and 90 day mortality. Overall costs of the perioperative care of CRS+HIPEC will be compared to CRS alone in our setting. Conclusions: Interval CRS+HIPEC is feasible, safe and cost effective for AEOC when performed collaboratively in a tertiary centre with a collocated peritoneal tumour service.